2008
DOI: 10.1017/s1352465808004542
|View full text |Cite
|
Sign up to set email alerts
|

Treating Socially Phobic Youth with CBT: Differential Outcomes and Treatment Considerations

Abstract: Social phobia (SP) is characterized by a fear of one or more social or performance situations. Studies of comorbidity in SP youth find anxiety and affective disorders co-occurring. The present study examined children with primary SP and compared them to children with primary Separation Anxiety Disorder (SAD) or Generalized Anxiety Disorder (GAD) prior to treatment and in response to treatment. The groups differed significantly on self-, parentand teacher-rated pretreatment measures. Additionally, the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 36 publications
6
55
0
Order By: Relevance
“…However, Kendall et al (2012) suggested several factors that can influence individual treatment outcome, including the presence of comorbid internalizing disorders (e.g., , and recommended further consideration of the effects of comorbid disorders on anxiety treatment outcomes given that such research will enhance our ability to specifically tailor interventions to meet individual presentations. Indeed, although some evidence has suggested that a diagnosis of social anxiety disorder is associated with less optimal treatment outcomes (Crawley, Beidas, Benjamin, Martin, & Kendall, 2008), this might be associated with this particular anxiety disorder's high rate of comorbidity with affective disorders , again underscoring the need for further study into differential treatment effects for the anxiety disorders and the effects of comorbidity, homo-, and heterotypic on treatment outcomes.…”
Section: Anxiety Disorders Update 105mentioning
confidence: 99%
“…However, Kendall et al (2012) suggested several factors that can influence individual treatment outcome, including the presence of comorbid internalizing disorders (e.g., , and recommended further consideration of the effects of comorbid disorders on anxiety treatment outcomes given that such research will enhance our ability to specifically tailor interventions to meet individual presentations. Indeed, although some evidence has suggested that a diagnosis of social anxiety disorder is associated with less optimal treatment outcomes (Crawley, Beidas, Benjamin, Martin, & Kendall, 2008), this might be associated with this particular anxiety disorder's high rate of comorbidity with affective disorders , again underscoring the need for further study into differential treatment effects for the anxiety disorders and the effects of comorbidity, homo-, and heterotypic on treatment outcomes.…”
Section: Anxiety Disorders Update 105mentioning
confidence: 99%
“…This is especially true for the comorbidity of depression and social anxiety in particular, both for symptoms of depression and social anxiety (and subclinical SAD) and disorders of MDD and SAD in youth (Crawley et al 2008;Essau et al 1999;Ranta et al 2009b;Viana et al 2008) and in adults . For example, epidemiological studies have found that 28-41% of youth with SAD also have comorbid depressive disorders, including MDD (Chavira et al 2004;Essau et al 1999;Ranta et al 2009b;Wittchen et al 1999).…”
Section: Comorbiditymentioning
confidence: 99%
“…That is, do children with SAD respond as well to treatment protocols as children with other anxiety disorders like generalised anxiety disorder or separation anxiety disorder? There has become increasing evidence that children with a diagnosis of social anxiety disorder have a slower response to CBT as well as poorer endpoints compared to children with other anxiety disorders (Crawley et al 2008 ;Compton et al 2014 ;Hudson et al 2015 ). This is not to say that the treatments are not effective for children with social anxiety disorder, rather it says that it is less effective than for children with other types of anxiety.…”
Section: Review Of the Efficacy Of Cbt For Adolescent Anxietymentioning
confidence: 99%